Rapamycin administration in humans blocks the contraction-induced increase in skeletal muscle protein synthesis - Drummond, Micah J.; Fry, Christopher S.; Glynn, Erin L.; Dreyer, Hans C.; Dhanani, Shaheen; Timmerman, Kyle L.; Volpi, Elena; Rasmussen, Blake B. (The Journal of physiology, 2009)
Muscle protein synthesis and mTORC1 signalling are concurrently stimulated following muscle contraction in humans. In an effort to determine whether mTORC1 signalling is essential for regulating muscle protein synthesis in humans, we treated subjects with a potent mTORC1 inhibitor (rapamycin) prior to performing a series of high-intensity muscle contractions. Here we show that rapamycin treatment blocks the early (1â2 h) acute contraction-induced increase (â¼40%) in human muscle protein synthesis. In addition, several downstream components of the mTORC1 signalling pathway were also blunted or blocked by rapamycin. For instance, S6K1 phosphorylation (Thr421/Ser424) was increased post-exercise 6-fold in the control group while being unchanged with rapamycin treatment. Furthermore, eEF2 phosphorylation (Thr56) was reduced by â¼25% post-exercise in the control group but phosphorylation following rapamycin treatment was unaltered, indicating that translation elongation was inhibited. Rapamycin administration prior to exercise also reduced the ability of raptor to associate with mTORC1 during post-exercise recovery. Surprisingly, rapamycin treatment prior to resistance exercise completely blocked the contraction-induced increase in the phosphorylation of ERK1/2 (Thr202/Tyr204) and blunted the increase in MNK1 (Thr197/202) phosphorylation. However, the phosphorylation of a known target of MNK1, eIF4E (Ser208), was similar in both groups ( P > 0.05) which is consistent with the notion that rapamycin does not directly inhibit MAPK signalling. We conclude that mTORC1 signalling is, in part, playing a key role in regulating the contraction-induced stimulation of muscle protein synthesis in humans, while dual activation of mTORC1 and ERK1/2 stimulation may be required for full stimulation of human skeletal muscle protein synthesis.